Innate lymphoid cells and parasites: Ancient foes with shared history. (29th January 2018) - Neill, D. R.; Fallon, P. G.
Summary: This special issue of Parasite Immunology charts the rapid advances made in our understanding of the myriad interactions between innate lymphoid cells and parasites and how these interactions have shaped our evolutionary history. Here, we provide an overview of the issue and highlight key findings from studies in mice and man.